Preparing to perform a resistance training workout - Kraemer, W. J.; Nitka, M. (Strength and Conditioning Journal, 2021)
Strength and conditioning professionals need to remember the fundamental principles of designing a resistance training workout. Designing a workout involves a host of decisions based on acute program variables. Choices made within each of these variables will impact the stimuli that the workout provides and the resulting adaptations.